ESTUDO DA RELAXAÇÃO DE TENSÕES RESIDUAIS EM CONDIÇÕES DE CARREGAMENTO CÍCLICO DA LIGA DE ALUMÍNIO 7050 – T7451 - Assai, Natany Dayani de Souza (2014)
The residual stress may decrease and redistribute through a process called relaxation. The relaxation of the residual stress is an important phenomenon in relation to the estimated fatigue resistance of the material and can occur due to static mechanical loading, thermal, cyclical and extension fatigue effects. Residual stresses are usually harmful for overlapping the operating voltage, while the fatigue resistance of metals and alloys can be improved by compressive residual stresses present in the surface layer by means of shot peening surface. The fatigue life with the compressive residual stress field caused by shot peening or sophisticated models for modeling voltage field Compressive Residual (CTRC) usually does not take into account the possibility of this change during the cyclic loading, ie , place the relaxation process, which also changes the fatigue life. This study aimed to obtain the residual stress profile relaxation by cyclic loading on aluminum alloy samples 7050- T7541 with shot peening glass and ceramics subjected to axial fatigue test. The technique for determining the residual stress was the X-ray diffraction for measuring accurately the redistribution of residual stresses along the depth of fatigue produced by the process. The removal of layers of material was performed by electrolytic attack. Hereby, it was possible to establish the relationship between the maximum stress and number of cycles in relation to the greater or lesser relaxation test specimens in different regimes of cyclic peening conditions with spherical glass and ceramics in the longitudinal and transverse directions. The results showed that the samples with the longitudinal direction shot peening redistribution showed higher compressive residual stresses in the transverse direction along the depth. For the samples of shot peening ceramic was virtually no relaxation on the surface only in depth when compared to the original profile, samples of ceramic shot peening obtained relaxation in remote locations of the surface, due to the influence of roughness. The redistribution of stresses for samples of shot peening glass were higher than those with shot peening ceramic along the depth in all cyclic regimens studied in the L and T directions. The residual stress relaxation occurred in both directions did not compromise beneficial effect of shot peening increase the fatigue life thereof, in relation to the base material.